1996
DOI: 10.1002/(sici)1096-9063(199612)48:4<343::aid-ps484>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Actions of the Cyclic Depsipeptide PF1022A and its Electrophysiological Effects on Muscle Cells of Ascaris suum

Abstract: The cyclic depsipeptide PF1022A, givea orally to mice, showed very good anthelmintic activity against Heligmosomoides polygyrus and Heterakis spwnosa at 50 mg kg-'. In uitro, PF1022A was very active against Trichinella spiralis and had good activity against Nippostrongylus brasiliensis at 1 pg d-'.An 18-membered enniatin analogue, JES 1798, showed good activity only against N . brasiliensis at 10 pg d-'. The optical antipode of PF1022A had poor activity even at 100 pg d-l. The effects of PF1022A on the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Since 1996, many efforts have been made to reveal the mechanism of action of PF1022A and emodepside using biochemical, electrophysiological and molecular biological tools as described in a variety of papers (Terada 1992;Pleiss et al 1995;Chen et al 1996;Martin et al 1996;Gessner et al 1996;Nicolay et al 2000;Willson et al 2001Willson et al , 2003Saeger et al 2001;Samson-Himmelstjerna et al 2005). …”
Section: Studies On the Mechanism Of Action Of Cyclic Octadepsipeptidesmentioning
confidence: 99%
“…Since 1996, many efforts have been made to reveal the mechanism of action of PF1022A and emodepside using biochemical, electrophysiological and molecular biological tools as described in a variety of papers (Terada 1992;Pleiss et al 1995;Chen et al 1996;Martin et al 1996;Gessner et al 1996;Nicolay et al 2000;Willson et al 2001Willson et al , 2003Saeger et al 2001;Samson-Himmelstjerna et al 2005). …”
Section: Studies On the Mechanism Of Action Of Cyclic Octadepsipeptidesmentioning
confidence: 99%
“…In contrast, the same authors reported a significant decrease in the activity of PF1022A when given parenterically. In mice, PF1022A is effective after oral application against Heligmosomoides polygyrus at 25 mg/kg and against Heterakis spumosa at 50 mg/kg (Martin et al 1996;Harder et al 1997;Bernt et al 1998). It has no activity against Trichinella spiralis muscle stages or the tapeworm Hymenolepis nana (unpublished observations).…”
Section: Anthelmintic Activity Of Cyclooctadepsipeptidesmentioning
confidence: 99%
“…In studies on the membrane potential and input conductance of the somatic muscle of Ascaris suum, using a two-microelectrode current-clamp technique, it could be shown that PF1022A does not antagonize the effects of the selective nicotinic agonist levamisole (Martin et al 1996). PF1022A, but not the optical antipode PF1022-001, produces a small, time-dependent increase in input conductance without potential change.…”
Section: Electrophysiological Studiesmentioning
confidence: 99%
“…Indeed, Terada (1992) has shown that PF 1022A stimulates GABAergic neurotransmission and simultaneously inhibits the cholinergic system. In addition, the depsipeptide induces a gradual chloride ion conductance in Ascaris suum muscle cells that is not seen with the anthelmintically inactive optical antipode (Martin et al 1996).…”
Section: Introductionmentioning
confidence: 94%
“…In the presence of PF 1022A a complete loss of the spike activity of Ascaris suum muscle was detectable within 5 h, which did not occur in the presence of the optical antipode of PF 1022A. Moreover, it has been shown that PF 1022A induces a gradually increasing chloride conductance in A. suum preparations, which does not occur in the presence of the optical antipode (Martin et al 1996). However, it has been demonstrated that PF 1022A is not a nicotinic antagonist in A. suum; thus, the inhibitory eect of this compound on the cholinergic system has not been explained.…”
Section: Light Microscopymentioning
confidence: 99%